Respuesta :

Answer:

(Choice A) 2(3d+3) & (Choice C) (3d+3)+(3d+3)

Step-by-step explanation:

[tex]4D + 6 + 2D = 6D + 6 = 2(3D + 3)[/tex] <--- A is correct

[tex]4D + 6 + 2D = 6D + 6 = 6(D +1)[/tex] < --- B is NOT correct

[tex]4D + 6 + 2D = 6D + 6 = 3d + 3d + 3 + 3 = (3d + 3)+(3d +3)[/tex] by associative and commutative properties

   so C is correct

A and C are both correct.

Answer:

Choices A and C

Step-by-step explanation:

Start by simplifying the original expression.

4d+6+2d

Combine like terms

6d+6

Now, we can check each expression to see if it is equivalent to 6d+6

Choice A:

2(3d+3)

Distribute the 2

2(3d)+2(3)

6d+6 --> It is equivalent!

Choice B:

6(d+6)

Distribute the 6

6(d)+6(6)

6d+36 --> No, it is not equivalent

Choice C

(3d+3)+(3d+3)

The parentheses aren't necessary so we can take them out.

3d+3+3d+3

Combine like terms

6d+6 --> It is equivalent!